Analysis of the prognostic and immune role of MCM6 in pan-cancer and experimental validation in lung adenocarcinoma cells - Minghua Liao; Chunyu Li; Jun Lv; Rui Yang; Jun Li; Ke Wu; Jiayi Zhang; Qian Zhu; Yingchang Shi; Xianming Zhang (Scientific Reports)
Abstract Mini-chromosome maintenance protein 6 (MCM6), a member of the DNA replication initiation complex, is considered a potential prognostic marker for multiple tumors. However, the biological role of MCM6 has not been reported in pan-cancer. In present study, a pan-cancer analysis of MCM6 was performed using multiple databases and online websites. The relationship between MCM6 and DNA methylation, prognosis, immune infiltration and immunotherapy response was investigated. Weighted gene co-expression network analysis (WGCNA) and least absolute shrinkage and selection operator (LASSO) Cox regression models were performed to construct prognostic risk signature for lung adenocarcinoma (LUAD) based on MCM6-related cell cycle genes (MrCCGs). Meanwhile, the biological function of MCM6 in lung adenocarcinoma was further verified through in vivo and in vitro experiments. MCM6 is highly expressed and is a prognostic risk factor in most tumors. MCM6 expression is significantly associated with the infiltration of immune cells (especially MDSCs) in a variety of tumors. The risk signature based on MrCCGs can reliably predict the prognosis of LUAD (AUC = 0.739). Immunohistochemical staining showed that the expression of MCM6 is higher in lung adenocarcinoma tissues compared with para-cancer tissues and is associated with the poor prognosis of lung adenocarcinoma patients. In vitro, MCM6 knockdown inhibited proliferation, invasion, and migration of A549 and H1299 cells, and blocked the G1 phase of the A549 cell cycle. In vivo, knockdown of MCM6 inhibited the growth of xenograft tumors in nude mice. The study suggests that MCM6 may be a potential prognostic and immunological biomarker in many cancers.